Sechium edule: Phytochemistry, Biological Activities, Potential Health Effects, Food-Industry Applications, and Future Perspectives - Muhammad Bilal; Asad Abbas; Ralf Weiskirchen; Hammad Hafeez; Muhammad Riaz; Andleeb Zahra; Arooj Fatima; Muhammad Khurram Afzal; Hassan Raza (Foods, 2026)
Sechium edule (Jacq.) Sw. (chayote), a neglected and underutilized Cucurbitaceae crop widely cultivated across tropical and subtropical regions, has drawn growing interest as a source of health-promoting food components. This review critically synthesizes studies published between 2000 and 2026 on its botanical features, genome characterization, nutritional value, phytochemistry, bioactivities, safety, and food-industry applications, based on literature retrieved from PubMed, Scopus, Web of Science, ScienceDirect, and the Cochrane Library. Different plant parts (fruits, leaves, seeds, tuberous roots, and peels) contain diverse bioactive compounds, including flavonoids, phenolic acids, cucurbitacins, pectin polysaccharides, and carotenoids. Reported bioactivities include antioxidant, anti-inflammatory, hypoglycemic, cardioprotective, antiproliferative, and geroprotective effects, mediated in part through Nrf2-mediated antioxidant signaling and sirtuin (SIRT1/3/5/6) upregulation. Notably, a systematic meta-analysis demonstrated a significant reduction in serum glucose (MD = −20.56; 95% CI: −29.35 to −11.77) and HbA1c following three months of chayote intake in patients with metabolic syndrome and type 2 diabetes. Industrially, chayote has been developed into fermented products, starch- and peel-derived bioactive films, ultrasound-extracted pectin, α-amylase inhibitory seed protein isolates, and probiotic encapsulation systems. Recent genomic work has further revealed a chromosome-level genome assembly, whole-genome duplication events, and a domestication history tracing to Mexico’s Oaxaca region. Collectively, this evidence positions chayote as a promising underutilized resource for food, nutraceutical, and biomedical use, while highlighting key gaps: the need for standardized clinical trials, bioavailability studies, and comprehensive safety evaluation.